2015
DOI: 10.3855/jidc.4700
|View full text |Cite
|
Sign up to set email alerts
|

Increasing frequency of Pseudomonas aeruginosa infections during tigecycline use

Abstract: Introduction: The widespread use of tigecycline raises the question of increasing infection rates of Pseudomonas aeruginosa (PA) in ICUs which are not affected by this antibiotic. Objective: The aim of this study was to determine if treatment with tigecycline is a risk factor for PA infection in ICU patients. Methodology: A retrospective and observational study was conducted at Erciyes University Hospital, Turkey, between 2008 and 2010. The Erciyes University Hospital is a 1300-bed tertiary care facility. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Similar investigation by Davane et al [2], revealed that 26 (52.0%) was found positive from the different environmental samples examined. A study by Ulu-Kilic et al [15] revealed that two hundred and seventy-eight (23.8%) of the patients investigated had P. aeruginosa infection during their ICU stay. Fifty-nine patients (21.2%) in the case group received tigecycline before developing P. aeruginosa infections, which were found to be significantly more frequent than in the controls (P < 0.01) [15].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar investigation by Davane et al [2], revealed that 26 (52.0%) was found positive from the different environmental samples examined. A study by Ulu-Kilic et al [15] revealed that two hundred and seventy-eight (23.8%) of the patients investigated had P. aeruginosa infection during their ICU stay. Fifty-nine patients (21.2%) in the case group received tigecycline before developing P. aeruginosa infections, which were found to be significantly more frequent than in the controls (P < 0.01) [15].…”
Section: Discussionmentioning
confidence: 98%
“…P. aeruginosa have been isolated from adult bacterial meningitis with underlying disease in Tokyo, Japan [9], a tertiary care teaching hospital, India [1], a 5-year surveillance of wound infections in Okada, Edo State [10], from ear, nose and throat among patients attending Aminu Kano Teaching Hospital, Nigeria [11], a tertiary care hospital of Jhalawar District, India [12], and sinks in the patient rooms and a retrospective case-control study in Germany [13]. In addition, studies on the influence of hospital waste water discharge and its potential microbial hazards have been investigated in Brazil [14], and increasing frequency of P. aeruginosa infections in Turkey was also investigated [15]. In this paper, we report on the characterization of antibiotic-resistant P. aeruginosa from hospital drains, as part of our larger study on the reservoirs of antibiotic resistance determinants in the environment.…”
Section: A Rt I C L E I N F Omentioning
confidence: 99%
“…The present results clearly show that challenging P. aeruginosa with tigecycline has clinically relevant consequences, despite this bacterial pathogen is considered to be intrinsically resistant to this antibiotic. Tigecycline is used for empiric treatment of Gram-negative infections, and in this type of patients, the main agent causing superinfection is P. aeruginosa ( Garcia-Cabrera et al, 2010 ; Ulu-Kilic et al, 2015 ; Katsiari et al, 2016 ), which is most likely under tigecycline selection during treatment. Our results indicate that tigecycline selects mutants presenting reduced susceptibility to antibiotics of clinical value as aztreonam, ceftazidime, ciprofloxacin or aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, tigecycline was used in the present study since it provides an opportunity to examine whether or not bacterial pathogens can acquire clinically relevant characteristics when challenged with the antibiotics to which they are considered to be intrinsically resistant. In this regard, it is worth mentioning that P. aeruginosa has emerged as a major cause of superinfection in nosocomial patients treated with tigecycline ( Garcia-Cabrera et al, 2010 ; Ulu-Kilic et al, 2015 ; Katsiari et al, 2016 ). Knowing whether or not the empirical use of tigecycline for treating Gram-negative hospital infections might challenge P. aeruginosa , affecting its susceptibility to other antibiotics commonly used for treating P. aeruginosa infections, is of relevance for developing a rational approach for treating such superinfections.…”
Section: Introductionmentioning
confidence: 99%
“…Responsible for slow nonspecific diffusion of solutes into the bacterium, it has been shown that OprF folds into two conformations, with less than 5% of the porin present in the openchannel conformer, severely limiting penetration of molecules into the bacterium (50). It is for this multitude of reasons that often agents which are active on most other Gram-negative bacteria are less effective on Pseudomonas aeruginosa (13,(51)(52)(53), and finding compounds that inhibit this organism can be difficult. Again, it is imperative to understand the roles efflux and permeability play in the intrinsic resistance of this organism when developing the next generation of antibiotics.…”
mentioning
confidence: 99%